2011
DOI: 10.1002/app.34862
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of thermal degradation of polysulfone/polyimide blended polymeric membranes

Abstract: Flat-sheet asymmetric polysulfone (PSF)/ polyimide (PI) blended membranes were fabricated by a phase-inversion technique. The fabricated membranes were characterized by Fourier transform infrared spectroscopy, differential scanning calorimetry, and field emission scanning electron microscopy analyses. The kinetics of thermal degradation of the membranes were studied from thermogravimetric data following Friedman's kinetic approach. The thermal degradation process of the membranes followed first-order rate kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 43 publications
3
10
0
Order By: Relevance
“…Interestingly, the E app values were similar while the structures of the monomer units were different [11,31], implying that the obtained E app values mainly indicated imide ring fission in the PI main chain. In addition, it is known that the pyrolysis of PI (i.e., the fission of the imide ring) commonly follows model F 1 (A 1 ) [13,31,32], suggesting that F 1 (A 1 ) was the most suitable one of the best three-fitting models. This suggested that the rate of imide ring fission is proportional to the concentration of the unreacted imide rings.…”
Section: Kinetic Analyses Of Pi Decomposition In Absence and Presencementioning
confidence: 98%
“…Interestingly, the E app values were similar while the structures of the monomer units were different [11,31], implying that the obtained E app values mainly indicated imide ring fission in the PI main chain. In addition, it is known that the pyrolysis of PI (i.e., the fission of the imide ring) commonly follows model F 1 (A 1 ) [13,31,32], suggesting that F 1 (A 1 ) was the most suitable one of the best three-fitting models. This suggested that the rate of imide ring fission is proportional to the concentration of the unreacted imide rings.…”
Section: Kinetic Analyses Of Pi Decomposition In Absence and Presencementioning
confidence: 98%
“…The weight loss observed at the beginning of TGA cycle indicates the presence of moisture or residual solvent in the membrane. 27,28 The presence of moisture or solvent can affect the separation performance of the membrane. It also indicates that there are weak molecular interactions between polymer chains and solvent used.…”
Section: Permeation Analysismentioning
confidence: 99%
“…These MMMs display some characteristic properties of both ceramic and organic polymers . To produce MMMs containing nanosilica, silica precursors such as tetraethyl orthosilicate (TEOS) is added due to controllable reaction rate and ease of processing . Sol–gel technique is capable of forming silica inorganic frameworks from TEOS under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Polysulfone (PSF) is reported to be a suitable option that possesses good thermo‐mechanical strength, acceptable gas performance and low cost. Its high resistance to plasticization up to 30 bars pressure, makes it a appropriate for membrane development . Nevertheless, to achieve improved properties, high performance polyimide (PI) is preferred.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation